ANALISIS ASPEK KESULITAN MENYELESAIKAN SOAL-SOAL STOIKIOMETRI BAGI SISWA KELAS X SMA NEGERI 6 PALU - Eka Anisyah Miftahul Jannah; Supriadi Supriadi; Suherman Suherman (Jurnal Akademika Kimia, 2017)
The difficult aspect of solving stoichiometry problems for class X student need more attention. The aim of this research is to provide an overview of students’ ability in solving stoichiometry problems from cognitive aspects, and to determine the subject and the degree of students difficulty in solving Stoichiometry problems. The research subjects are students of class X Senior High School 6 Palu of the school year 2012/2013.The research sample consisted of two classes, namely Xa classes with 17 students and classes Xd with 17 students. An essay test with 13 items of question which has been validated by the school teacher are the instrument. The results of this descriptive study shown that difficulties students in the C1 cognitive aspect (Knowledge) about 11.86% with very low category, C2 (Comprehension) of 42.08% with moderate category and C3 (Application Concept) about 62.29% with a high category, and the student’s difficulties in determining the amount of moles about 46.68% with moderate category, in determining the molar mass about 36.85% with low category, the molar volume about 44.61% with a medium category, in understanding and applying Avogadro’s hypothesis and the number of moles of gas about 44.61% with moderate categories, in determining empirical formula and molecular formula about 58.96% with moderate category, hydrate compounds about 64.63% with high category, percentage of elements in compound about 56.15% with medium category, limiting reagent about 67.86% with the high category, the number of reactants or reaction products 80.10% with the high category. The conclusion is that the most difficult aspects of cognition are at C3 (Application Concepts), and the most difficult subject is to determine limiting reagents and hydrate compounds.